Stratified survival of resected and overall pancreatic cancer patients in Europe and the USA in the early twenty-first century: a large, international population-based study - Huang, Lei; Balavarca, Yesilda; Schrotz-King, Petra; Brenner, Hermann (BMC medicine, 2018)
Background - The prognosis of pancreatic cancer (PaC) strongly varies across different stages and age groups, which has unfortunately not been well recorded in the literature. This international population-based study aimed to provide tumor-node-metastasis (TNM) stage- and age-specific survival estimates and trends in resected and overall (resected and unresected) PaC in the early twenty-first century. - Methods - Using data from the US Surveillance, Epidemiology, and End Results-18 Program and the national cancer registries of the Netherlands, Belgium, Norway, and Slovenia, short-term and long-term overall survival results stratified by TNM stage and age in resected and overall primary PaC, irrespective of being microscopically confirmed or not, in 2003-2014 were computed using the Kaplan-Meier method. The temporal survival trends over three predefined periods (2003-2005, 2006-2008, and 2009-2011) were further examined using the log-rank test. - Results - In total, data for 125,183 patients were analyzed. Overall, age-stratified 3-year survival was 20-34% (< 60 years), 14-25% (60-69 years), and 9-13% (≥ 70 years) in stages I-II PaC; and 2-5% (< 60 years), 1-2% (60-69 years), and < 1-1% (≥ 70 years) in stages III-IV cancer. Patients who underwent operation had higher 3-year survival in each stage and age group (stages I-II: 23-39% (< 60 years), 16-31% (60-69 years), and 17-30% (≥ 70 years); stages III-IV: 5-19% (< 70 years) and 2-14% (≥ 70 years)). Perioperative survival also decreased with advancing stage and older age (stages I-II: 98-100% (< 60 years), 97-99% (60-69 years), and 94-99% (≥ 70 years); stages III-IV: 94-99% (< 70 years) and 81-96% (≥ 70 years)). Between 2003 and 2005 and 2009-2011, for overall PaC, both short-term and long-term survival improvements were observed in all countries except Belgium; for resected disease, short-term improvements were present only in the USA and Slovenia, but long-term improvements were observed in all countries except Slovenia, with stage-specific variations. - Conclusions - Our large international study provides TNM stage- and age-specific population-based survival in overall and resected PaC that will facilitate clinical counseling. While the survival expectations for patients with resected PaC are substantially higher than the widely available and known dismal survival predictions for overall patients, conclusions on the benefits of resection cannot be made from this observational study. Patients with advanced-stage disease and/or older age should undergo careful risk assessment before treatment. Limited but inspiring improvement in survival is observed. - Electronic supplementary material - The online version of this article (10.1186/s12916-018-1120-9) contains supplementary material, which is available to authorized users.